Adherence to European Society of Gastrointestinal Endoscopy recommendations of endoscopists performing small bowel capsule endoscopy in Italy. Issue 6 (June 2019) - Rondonotti, Emanuele; Spada, Cristiano; Pennazio, Marco; de Franchis, Roberto; Cadoni, Sergio; Girelli, Carlo; Hassan, Cesare; Marmo, Riccardo; Riccioni, Maria Elena; Scarpulla, Giuseppe; Soncini, Marco; Vecchi, Maurizio; et al.
Abstract: Background: The European Society of Gastrointestinal Endoscopy (ESGE) has recently issued a technical review focused on small bowel capsule endoscopy (SBCE). Aim: To compare SBCE current practice in Italy to ESGE technical recommendations. Material and methods: A dedicated per-centre semi-quantitative questionnaire was prepared by a group of SBCE experts. One-hundred-fifty Centres were invited to participate in the data collection concerning SBCEs performed between June 2016 and June 2017. Data were compared with ESGE recommendations. Results: 120 Centres participated in the data collection. Current practices agreed with ESGE recommendations in 56.3% (9/16) of the issues evaluated. Differences between ESGE recommendations and current practice concerned the management of patients with pacemakers or cardiac implantable defibrillators (which was in agreement with ESGE recommendations in 31.7% and 15.8% of Centres, respectively), the SBCE setting (only 51% of SBCEs were performed as outpatients procedures), the assessment of capsule excretion (timing and modality were in agreement with ESGE recommendation in 20.0% of Centres), and in the involvement of trained nurses or fellows in training as pre-readers (7/120; 5.8%). Conclusions: Although SBCE is widely used and largely available in Italy, there are still some technical, practical and organizational issues that can be modified to bridge the gap between current practice and ESGE guideline recommendations.